INVENTARISASI HAMA ULAT KANTUNG DAN PARASITOID DI PERKEBUNAN KELAPA SAWIT PT. KARYA TANAH SUBUR (KTS) ACEH BARAT - Chairudin Chairudin; Rini Aprilna; Sumeinika Fitria Lizmah; Agustinur Agustinur; Vina Maulidia (Agros Journal of Agriculture Science, 2024)
Bagworms are one of the important pests in oil palm cultivation. Bagworm causes holes in oil palm leaves, slits and even dry out, which can cause damage and reduce productivity. Conventional control of bagworm pests using insecticides has been proven to cause long-term losses, so more environmentally friendly control is needed by using parasitoids. This research aims to inventory bagworm pests and parasitoids in oil palm plantations which have the potential to be developed for ecosystem-based pest control purposes. Sampling in this research was carried out at PT Karya Tanah Subur oil palm plantation, West Aceh. The analysis was carried out by calculating the diversity and evenness of pest and parasitoid types. From the research results, 4 types of bagworms were obtained, identified as Metisa plana, Mahasena corbetti, Clania sp. and Cremastopsyche pendula. Of the 4 types of bagworms, the more dominant ones are Metisa plana and Mahasena corbetti. Meanwhile, there are also 4 types of parasitoids found, identified as Diadegma sp., Dirhinus sp., Paraphylax varius and Telenomus sp.